Method for preparing engineering material brick by detoxifying and treating pollution of metal chromium smelting slag
Patent Information
- Application Number
- CN202610084621.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-22
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2046-01-22
AI Technical Summary
第三步,分析六价铬含量,根据六价铬含量配入还原剂铝、镁,还原剂粒度﹤100目;混料、压块、烘干;高温煅烧,恒温温度为1200—1300℃,恒温时间为6—8小时,冷却至低于100℃,然后,按照破碎、取样分析总铬、六价铬、钡含量,最后检测刚玉砖密度和耐火度:解毒后刚玉砖产品密度3.4—4.6克/厘米3,密实,无孔洞,成分为氧化铝、氧化铬,耐火度﹥1800℃。
Smart Images

Figure CN121948986B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing refractory bricks after detoxifying metallic chromium smelting slag, and more particularly to a method for preparing engineering material bricks after detoxifying metallic chromium smelting slag contamination. This method involves reducing hexavalent chromium to trivalent chromium to detoxify metallic chromium smelting slag before preparing engineering material bricks. Background Technology
[0002] Metallic chromium, due to its high melting point, high strength, corrosion resistance, and wear resistance, especially its strong corrosion resistance at high temperatures, is widely used as an additive in steel metallurgy, high-temperature alloys, resistance alloys, and precision alloys. It is particularly indispensable in the smelting of non-ferrous chromium-containing alloys, making metallic chromium a strategic national product. In this process, metallic aluminum is oxidized to alumina, while chromium oxide is reduced to metallic chromium and sinks to the bottom of the furnace. The floating layer is slag containing alumina and chromium oxide; this is the metallic chromium smelting slag. The smelting temperature is 2200–2400℃.
[0003] The composition of chromium trioxide is: Cr2O3 ≥ 98%, Fe2O3 ≤ 0.17%, Si2O2 ≤ 0.20%, S ≤ 0.009%, C ≤ 0.008%; The composition of metallic chromium is: Cr ≥ 99%, Fe ≤ 0.3%, Si ≤ 0.25%, Al ≤ 0.30%, C ≤ 0.01%.
[0004] In the production of chromium salts (including chromium trioxide), the raw material is chromium ore. A roasting method is used, in which soda ash and chromium ore are roasted at high temperature to produce sodium chromate. The sodium chromate is then introduced into the solution by leaching, and the leached chromium residue containing hexavalent chromium is separated out.
[0005] Composition of leached chromium slag (weight %): Cr2O3: 8-12%, Al2O3: 18-24%, Fe2O3: 36-46%, MgO: 10-16%, CaO: 1.5-3.5%, water-soluble Cr (hexavalent): 0.5-1.5%, acid-soluble Cr (hexavalent): 0.4-1%, density: 1.2-2.2 g / cm3, melting point of leached chromium slag: 1400-1600℃, approximately 1 ton of leached chromium slag is produced for every ton of sodium dichromate (sodium dichromate molecular formula: Na2Cr2O7 ▪2H2O).
[0006] The patent for a comprehensive utilization method and dedicated system for the harmless treatment of chromium slag (publication number: CN 106316434A) does not treat acid-soluble chromium. After being used as a refractory material, the lattice and film encapsulating the acid-soluble chromium are destroyed, causing hexavalent chromium to exceed the standard again. The chromium slag detoxified by this method is suitable for landfill and can be sealed and isolated with geomembrane.
[0007] Patent publication number WO2021 / 010312A1 describes the production of low-carbon ferrochrome using chromium ore as raw material and silicon as a reducing agent, which is carried out in a molten state. If carried out in a molten state in an electric furnace, the metallic chromium smelting slag needs to be melted at a temperature of 2000-2200℃, resulting in high electricity consumption, high cost, low output, and large fixed asset investment.
[0008] Current methods for detoxifying chromium smelting slag involve using petroleum coke as a reducing agent in a three-stage electric arc furnace. The reduction temperature is 2000-2200℃, and the reduction time is 8-12 hours. The detoxified products are chromium carbide containing over 90% chromium and approximately 5% carbon, as well as alumina containing a certain amount of carbon. This method is energy-intensive, and the high carbon content of the alumina has several adverse effects on its use. For example… Figure 1 The process is shown in the diagram.
[0009] Another method involves washing granular metallic chromium smelting slag with large amounts of water, which can only remove water-soluble hexavalent chromium from the surface. When the surface of the particles is damaged during subsequent use, the hexavalent chromium levels still exceed the standard.
[0010] Chromium leaching slag can also be achieved by leaching hexavalent chromium with hydrochloric acid or sulfuric acid. Subsequently, a wet detoxification process is performed in the solution using reducing agents, such as ferrous sulfate or sodium sulfide. After this process, the slag can no longer be used.
[0011] Composition of metallic chromium smelting slag (weight %): Cr2O3: 13-17%, Al2O3: 80%-85%, Fe2O3: 0.02%-0.1%, MgO: 0.1%-0.2%, CaO: 0.2%-1.5%, water-soluble Cr (hexavalent): 0.01%-0.03%, acid-soluble Cr (hexavalent): 0.01%-0.02%, density: 3.2-4.2 g / cm³, melting point of metallic chromium smelting slag: 2100-2300℃ (700-900℃ higher than the melting point of leached chromium slag) The blast furnace reduction process for treating chromium slag (patent publication number: CN 101397607A) involves reducing leached chromium slag containing hexavalent chromium in a blast furnace. Part of the slag is reduced to trivalent chromium, and the rest to zero-valent chromium. The portion reduced to trivalent chromium forms slag. Because chromium trioxide has a high melting point of 2265℃, the slag has a high melting point and is difficult to tap from the furnace. Chromium has a melting point of 1758℃, and even at a specific temperature of 1200℃, molten ferrochrome is difficult to tap from the furnace.
[0012] The aluminothermic process for producing metallic chromium generates a large amount of hazardous solid waste, chromium smelting slag. Approximately 1.3 tons of chromium smelting slag are produced for every ton of metallic chromium produced. With increasing national emphasis on environmental protection, particularly stringent requirements for the discharge of waste gas, wastewater, and solid waste, enterprises must detoxify any hazardous solid waste they discharge before it can be reused. Summary of the Invention
[0013] The purpose of this invention is to provide a method for preparing engineering material bricks after detoxifying chromium smelting slag. This method involves reducing hexavalent chromium to trivalent chromium, thus detoxifying the chromium slag and preparing engineering material bricks. The method reduces hexavalent chromium (including acid-soluble hexavalent chromium) to trivalent chromium, meeting the requirements of the "Technical Specification for Environmental Protection of Chromium Slag Pollution Control (Provisional)" (HJ / T301-2007). The leaching limits are: total chromium < 9 mg / L, hexavalent chromium < 3 mg / L, and barium < 50 mg / L, transforming the chromium smelting slag from hazardous solid waste into ordinary solid waste. In particular, by controlling the process conditions and parameters, the pollution control limits for bricks and blocks produced using chromium slag (Table 5 in the specification) are achieved: total chromium < 0.3 mg / L, hexavalent chromium < 0.1 mg / L, and barium < 4.0 mg / L. Furthermore, resource reuse is achieved, resulting in corundum bricks with a density of 3.4–4.6 g / cm³ and a refractoriness > 1800℃. Detoxified corundum slag bricks are used as refractory materials.
[0014] The objective of this invention is achieved through the following technical solution: A method for preparing engineering material bricks after detoxifying chromium smelting slag contamination, the method comprising the following preparation steps: (The method involves reducing hexavalent chromium to trivalent chromium and then detoxifying the chromium slag contamination.) Step 1: Dissolving hexavalent chromium by acid leaching. Strong acid is used to disrupt the crystal lattices of dicalcium silicate, calcium aluminoferrite, and calcium aluminate, effectively reducing hexavalent chromium. After crushing the metallic chromium smelting slag to 0-2 mm, the slag is soaked in strong phosphoric acid to dissolve the acid-soluble chromium. The weight ratio of metallic chromium smelting slag to phosphoric acid is: metallic chromium smelting slag : phosphoric acid = 100 : (3-10). The soaking time after mixing the metallic chromium smelting slag and phosphoric acid is 24 hours. The second step involves adding strong reducing agents such as aluminum and magnesium, mixing thoroughly, then pressing, drying, and detoxifying the mixture. After soaking in phosphoric acid for 24 hours, powdered aluminum and magnesium are added to the metallic chromium smelting slag as reducing agents, and a reduction reaction is carried out under high-temperature conditions. 2Al + 2CrO3 = Cr2O3 + Al2O3 3Mg + 2CrO3 = Cr2O3 + 3MgO The third step involves analyzing the hexavalent chromium content. Based on this content, reducing agents aluminum and magnesium are added, with a particle size <100 mesh. The mixture is then pressed into blocks and dried. High-temperature calcination is performed at a constant temperature of 1200-1300℃ for 6-8 hours, followed by cooling to below 100℃. Then, the blocks are crushed, and samples are taken for analysis of total chromium, hexavalent chromium, and barium content. Finally, the density and refractoriness of the corundum bricks are tested: after detoxification, the density of the corundum bricks is 3.4-4.6 g / cm³, dense, without pores, and composed of alumina and chromium oxide, with a refractoriness >1800℃.
[0015] The advantages and effects of this invention are: 1. This invention employs an aluminum-magnesium reduction method for detoxification, using aluminum to reduce chromium trioxide, resulting in the slag produced during the production of metallic chromium. The detoxification target described in this invention is the metallic chromium smelting slag produced during the reduction of chromium trioxide with aluminum in metallic chromium smelting, which is not the same substance as leached chromium slag. This invention performs detoxification at a solid-state temperature of 1200-1300℃, saving 50% of energy compared to detoxification at 2000-2200℃.
[0016] 2. The strong acid leaching process of this invention destroys the crystal lattice and thin film encapsulating hexavalent chromium, and then uses strong reducing agents such as aluminum and magnesium as reducing agents, which have a stronger reducing ability than carbon, more thorough detoxification, and no rebound.
[0017] 3. In the chromium smelting slag of this invention, the alumina content reaches 80%, in the form of aluminum corundum, and enters the slag; the ferric oxide content is less than 2%. 4. This invention detoxifies hexavalent chromium in a solid state by reducing it, using aluminum and magnesium as reducing agents, resulting in strong reducing power. The invention uses phosphoric acid to leach and dissolve hexavalent chromium, followed by the use of metallic aluminum and magnesium as reducing agents, without introducing other impurities. The detoxified corundum slag can also be used as refractory material, with a refractoriness >1800℃. The detoxified corundum slag bricks, used as refractory materials, achieve resource reuse. Attached Figure Description
[0018] Figure 1 This is a diagram illustrating the existing leaching process for separating hexavalent chromium slag from sodium chromate in a solution. Figure 2 This invention provides a process diagram for reducing hexavalent chromium to trivalent chromium to meet the environmental technical specifications and standards for chromium slag pollution control. Detailed Implementation
[0019] The present invention will now be described in detail with reference to the embodiments shown in the accompanying drawings.
[0020] This invention discloses a method for preparing engineering material bricks after detoxifying chromium smelting slag. The method reduces hexavalent chromium to trivalent chromium, meeting the environmental technical specifications for chromium slag pollution control. The process includes the following steps: Step 1: Dissolution of acid-soluble hexavalent chromium. In the detoxification process of leaching chromium slag and metallic chromium smelting slag, acid-soluble chromium has a significant impact on the detoxification effect. Water-soluble hexavalent chromium and acid-soluble hexavalent chromium differ greatly in their hazard and treatment difficulty. Phase analysis of leaching chromium slag and metallic chromium smelting slag shows that dicalcium silicate-calcium chromate, calcium aluminoferrite-calcium chromate, and calcium aluminate-calcium chromate exist within the crystal lattices of dicalcium silicate, calcium aluminoferrite, and calcium aluminate. To eliminate this acid-soluble hexavalent chromium, strong acids must be used to disrupt the crystal lattices of dicalcium silicate, calcium aluminoferrite, and calcium aluminate to effectively reduce the hexavalent chromium. If the acid-soluble hexavalent chromium is not reduced, the detoxification is incomplete. If the detoxified chromium slag is heated in water for a long time, or exposed to rainwater and carbon dioxide outdoors for extended periods, the acid-soluble chromium will slowly transform into water-soluble chromium as calcium silicate, calcium aluminoferrite, and calcium aluminate dissolve or hydrate (weather). This will cause the detoxified slag to revert to hazardous solid waste. Therefore, after crushing the chromium smelting slag into 0-2 mm pieces, it is soaked in strong acid phosphoric acid to dissolve the acid-soluble chromium in the slag. The weight ratio of chromium smelting slag to phosphoric acid is: chromium smelting slag : phosphoric acid = 100 : (3-10). After mixing the chromium smelting slag and phosphoric acid, the soaking time is 24 hours. The second step involves adding strong reducing agents such as aluminum and magnesium, mixing thoroughly, then pressing, drying, and detoxifying the chromium smelting slag that has been soaked in phosphoric acid for 24 hours. Powdered aluminum and magnesium are then added as reducing agents, and a reduction reaction is carried out under high-temperature conditions. 2Al + 2CrO3 = Cr2O3 + Al2O3 3Mg + 2CrO3 = Cr2O3 + 3MgO The third step involves analyzing the hexavalent chromium content. Based on this content, appropriate amounts of reducing agents, aluminum and magnesium, are added. The reducing agent particle size is <100 mesh. The mixture is then pressed into briquettes, dried, and calcined at a high temperature of 1200-1300℃ for 6-8 hours. After cooling to below 100℃, the briquettes are crushed, and samples are taken for analysis of total chromium, hexavalent chromium, and barium content. The density and refractoriness of the corundum bricks are also tested. After detoxification, the density of the corundum brick product is 3.4-4.6 g / cm³, dense, and without pores. Its components are alumina and chromium oxide, and it can be used as corundum bricks with a refractoriness >1800℃. After detoxification, it becomes refractory corundum slag bricks.
[0021] The specific implementation plan is as follows: Example 1
[0022] Step 1: Dissolving hexavalent chromium by acid leaching. The chromium smelting slag was crushed and passed through a 2mm sieve. A leachate was prepared according to the requirements of the "Technical Specification for Environmental Protection of Chromium Slag Pollution Control (Provisional)" (HJ / T301-2007) and tested. The hexavalent chromium concentration was 191 mg / L, classifying it as hazardous solid waste. The chromium smelting slag and phosphoric acid were mixed in a weight ratio of 100:5 and soaked for 24 hours.
[0023] Step 2: Reduction and detoxification are carried out using aluminum powder as a reducing agent. The aluminum powder particle size is 100 mesh, and the amount of aluminum powder added is 1.2% of the dry basis smelting slag weight. The aluminum powder and the chromium smelting slag soaked in phosphoric acid are mixed evenly using a mixer, and then pressed into 6 pieces using a press. Each piece is 460mm×150mm×75mm in size. They are placed in a drying oven for 24 hours to dry, and then placed in a calcining furnace at a constant temperature of 1250℃ for 6 hours. After cooling, the leachate is prepared and tested according to the requirements of the Interim Technical Specification for Environmental Protection of Chromium Slag Pollution Control (HJ / T301-2007). The total chromium is 0.1mg / L, hexavalent chromium is 0.09mg / L, and barium is 0.2mg / L. All indicators are lower than the pollution control index limits for bricks and blocks produced using chromium slag in the technical specification.
[0024] Step 3: Test the density and refractoriness of corundum. The density of the corundum brick is 3.6 g / cm³, which is dense and non-porous. The refractoriness is 1820℃. The detoxified corundum slag bricks are used as refractory materials. Example 2
[0025] Step 1: Dissolving hexavalent chromium by acid leaching. The smelting chromium slag was crushed and passed through a 2mm sieve. The leachate was prepared according to the requirements of the Interim Technical Specification for Environmental Protection of Chromium Slag Pollution Control (HJ / T301-2007) and tested. The hexavalent chromium concentration was 386 mg / L, which is classified as hazardous solid waste.
[0026] The chromium smelting slag and phosphoric acid were mixed in a weight ratio of 100:8 (chromium smelting slag: phosphoric acid = 100:8) and then soaked for 24 hours. Step 2: Reduction and detoxification are carried out using aluminum powder as a reducing agent. The aluminum powder particle size is 100 mesh, and the amount of aluminum powder added is 1.7% of the dry basis smelting slag weight. The aluminum powder and the chromium smelting slag soaked in phosphoric acid are mixed evenly using a mixer, and then pressed into 6 pieces using a press. Each piece is 460mm×150mm×75mm in size. They are placed in a drying oven for 24 hours to dry, and then placed in a calcining furnace at a constant temperature of 1280℃ for 7 hours. After cooling, the leachate is prepared and tested according to the requirements of the Interim Technical Specification for Environmental Protection of Chromium Slag Pollution Control (HJ / T301-2007). The total chromium is 0.15mg / L, hexavalent chromium is 0.05mg / L, and barium is 0.2mg / L. All indicators are lower than the pollution control limits for bricks and blocks produced using chromium slag in the technical specification.
[0027] Step 3: Test the density and refractoriness of the corundum bricks. The density of corundum is 4.2 g / cm³, it is dense and without pores. The refractoriness is 1860℃. The detoxified corundum slag bricks are used as refractory materials. Example 3
[0028] Step 1: Dissolving hexavalent chromium by acid leaching. The smelting chromium slag was crushed and passed through a 2mm sieve. The leachate was prepared according to the requirements of the Interim Technical Specification for Environmental Protection of Chromium Slag Pollution Control (HJ / T301-2007) and tested. The hexavalent chromium concentration was 260mg / L, which is classified as hazardous solid waste.
[0029] The chromium smelting slag and phosphoric acid were mixed in a weight ratio of 100:6, and the soaking time was 24 hours.
[0030] Step 2: Reduction and detoxification are carried out using aluminum powder as a reducing agent. The aluminum powder particle size is 100 mesh, and the amount of aluminum powder added is 1.4% of the dry basis smelting slag weight. The aluminum powder and the chromium smelting slag soaked in phosphoric acid are mixed evenly using a mixer, and then pressed into 6 pieces using a press. Each piece is 460mm×150mm×75mm in size. They are placed in a drying oven for 24 hours to dry, and then placed in a calcining furnace at a constant temperature of 1250℃ for 8 hours. After cooling, the leachate is prepared and tested according to the requirements of the Technical Specification for Environmental Protection of Chromium Slag Pollution Control (Provisional) (HJ / T301-2007). The total chromium is 0.12mg / L, hexavalent chromium is 0.02mg / L, and barium is 0.2mg / L. All indicators are lower than the pollution control index limits for bricks and blocks produced using chromium slag in the technical specification.
[0031] Step 3: Test the density and refractoriness of corundum. The density of corundum is 3.8 g / cm³, it is dense and without pores. The refractoriness is 1830℃. The detoxified corundum slag bricks are used as refractory materials. Example 4
[0032] Step 1: Dissolving hexavalent chromium by acid leaching. The smelting chromium slag was crushed and passed through a 2mm sieve. The leachate was prepared according to the requirements of the Interim Technical Specification for Environmental Protection of Chromium Slag Pollution Control (HJ / T301-2007) and tested. The hexavalent chromium concentration was 161 mg / L, which is classified as hazardous solid waste.
[0033] The chromium smelting slag and phosphoric acid were mixed in a weight ratio of 100:4 (chromium smelting slag: phosphoric acid = 100:4) and then soaked for 24 hours. Step 2: Reduction and detoxification are carried out using aluminum powder as a reducing agent. The aluminum powder particle size is 100 mesh, and the amount of aluminum powder added is 1% of the dry basis smelting slag weight. The aluminum powder and the chromium smelting slag soaked in phosphoric acid are mixed evenly using a mixer, and then pressed into 6 pieces using a press. Each piece is 460mm×150mm×75mm in size. They are placed in a drying oven for 24 hours to dry, and then placed in a calcining furnace at a constant temperature of 1210℃ for 6 hours. After cooling, the leachate is prepared and tested according to the requirements of the Interim Technical Specification for Environmental Protection of Chromium Slag Pollution Control (HJ / T301-2007). The total chromium is 0.16mg / L, hexavalent chromium is 0.03mg / L, and barium is 0.2mg / L. All indicators are lower than the pollution control limits for bricks and blocks produced using chromium slag in the technical specification.
[0034] Step 3: Test the density and refractoriness of the corundum bricks. The density of corundum is 3.7 g / cm³, it is dense and without pores. The refractoriness is 1860℃. The detoxified corundum slag bricks are used as refractory materials. Example 5
[0035] Step 1: Dissolving hexavalent chromium by acid leaching. The smelting chromium slag was crushed and passed through a 2mm sieve. The leachate was prepared according to the requirements of the Interim Technical Specification for Environmental Protection of Chromium Slag Pollution Control (HJ / T301-2007) and tested. The hexavalent chromium concentration was 769 mg / L, which is classified as hazardous solid waste.
[0036] The chromium smelting slag and phosphoric acid were mixed in a weight ratio of 100:8, and the soaking time was 24 hours.
[0037] Step 2: Reduction and detoxification are carried out using aluminum powder and magnesium powder as reducing agents. The aluminum powder particle size is 100 mesh sieve, and the amount of aluminum powder added is 1% of the dry basis smelting slag weight. The magnesium powder particle size is 100 mesh sieve, and the amount of magnesium powder added is 1% of the dry basis smelting slag weight. The aluminum powder, magnesium powder, and phosphoric acid-soaked metallic chromium smelting slag are mixed evenly using a mixer. The mixture is then pressed into 6 pieces using a press, each measuring 460mm × 150mm × 75mm. These pieces are dried in a drying oven for 24 hours, and then placed in a calcining furnace at a constant temperature of 1300℃ for 6 hours. After cooling, the leachate is prepared and tested according to the requirements of the Interim Technical Specification for Environmental Protection of Chromium Slag Pollution Control (HJ / T301-2007). The total chromium content is 0.2mg / L, hexavalent chromium is 0.08mg / L, and barium is 0.2mg / L. All indicators are lower than the pollution control limits for bricks and blocks produced using chromium slag in the technical specification.
[0038] Step 3: Test the density and refractoriness of corundum. The density of the corundum brick is 4.4 g / cm³, which is dense and non-porous. The refractoriness is 1860℃. The detoxified corundum slag bricks are used as refractory materials.
Claims
1. A method for preparing engineering material bricks after detoxification treatment of chromium smelting slag, characterized in that, The method includes the following steps: Step 1: Dissolving hexavalent chromium by acid leaching. The chromium smelting slag was crushed and passed through a 2mm sieve to prepare a leachate for testing. The hexavalent chromium concentration was 191 mg / L. The chromium smelting slag and phosphoric acid were mixed in a weight ratio of 100:5 and soaked for 24 hours. Step 2: Reduction and detoxification were carried out using aluminum powder as a reducing agent. The aluminum powder particle size was 100 mesh sieve, and the amount of aluminum powder added was 1.2% of the dry basis smelting slag weight. The aluminum powder and the chromium smelting slag soaked in phosphoric acid were mixed evenly using a mixer. The mixture was then pressed into 6 pieces using a press, each piece measuring 460mm×150mm×75mm. The pieces were placed in a drying oven for 24 hours to dry, and then placed in a calcining furnace at a constant temperature of 1250℃ for 6 hours to prepare corundum slag bricks. After cooling, a leachate was prepared and tested. The results showed that the total chromium was 0.1mg / L, hexavalent chromium was 0.09mg / L, and barium was 0.2mg / L. Step 3: Test the density and refractoriness of corundum slag bricks. The density of corundum slag bricks is 3.6 g / cm3, which is dense and without pores; the refractoriness is 1820℃; after detoxification, corundum slag bricks are used as refractory materials; in the metallic chromium smelting slag, the alumina content reaches 80% and the ferric oxide content is less than 2%; the alumina in the metallic chromium smelting slag is in the form of aluminum corundum.
2. A method for preparing engineering material bricks after detoxifying chromium smelting slag, characterized in that, The method includes the following steps: Step 1: Dissolving hexavalent chromium by acid leaching. The chromium smelting slag was crushed and passed through a 2mm sieve to prepare a leachate for testing. The hexavalent chromium concentration was 386 mg / L. The chromium smelting slag and phosphoric acid were mixed in a weight ratio of 100:8 and soaked for 24 hours. Step 2: Reduction and detoxification were carried out using aluminum powder as a reducing agent. The aluminum powder particle size was 100 mesh sieve, and the amount of aluminum powder added was 1.7% of the dry basis smelting slag weight. The aluminum powder and the chromium smelting slag soaked in phosphoric acid were mixed evenly using a mixer. The mixture was then pressed into 6 pieces using a press, each piece measuring 460mm×150mm×75mm. The pieces were placed in a drying oven for 24 hours to dry, and then placed in a calcining furnace at a constant temperature of 1280℃ for 7 hours to prepare corundum slag bricks. After cooling, a leachate was prepared and tested. The results showed that the total chromium was 0.15mg / L, hexavalent chromium was 0.05mg / L, and barium was 0.2mg / L. Step 3: Test the density and refractoriness of corundum slag bricks. The density of corundum slag bricks is 4.2 g / cm3, which is dense and without pores; the refractoriness is 1860℃; after detoxification, corundum slag bricks are used as refractory materials; in the metallic chromium smelting slag, the alumina content reaches 80% and the ferric oxide content is less than 2%; the alumina in the metallic chromium smelting slag is in the form of aluminum corundum.
3. A method for preparing engineering material bricks after detoxification treatment of chromium smelting slag, characterized in that, The method includes the following steps: Step 1: Dissolving hexavalent chromium by acid leaching. The chromium smelting slag is crushed and passed through a 2mm sieve to prepare a leachate for testing. The hexavalent chromium concentration is 260 mg / L. The chromium smelting slag and phosphoric acid are mixed in a weight ratio of 100:6 and soaked for 24 hours. Step 2: Reduction and detoxification were carried out using aluminum powder as a reducing agent. The aluminum powder particle size was 100 mesh sieve, and the amount of aluminum powder added was 1.4% of the dry basis smelting slag weight. The aluminum powder and the chromium smelting slag soaked in phosphoric acid were mixed evenly using a mixer. The mixture was then pressed into 6 pieces using a press, each piece measuring 460mm×150mm×75mm. The pieces were placed in a drying oven for 24 hours to dry, and then placed in a calcining furnace at a constant temperature of 1250℃ for 8 hours. Corundum slag bricks were thus prepared. After cooling, a leachate was prepared and tested. The results showed that the total chromium was 0.12mg / L, hexavalent chromium was 0.02mg / L, and barium was 0.2mg / L. Step 3: Test the density and refractoriness of corundum slag bricks. The density of corundum slag bricks is 3.8 g / cm3, which is dense and without pores; the refractoriness is 1830℃; after detoxification, corundum slag bricks are used as refractory materials; in the metallic chromium smelting slag, the alumina content reaches 80% and the ferric oxide content is less than 2%; the alumina in the metallic chromium smelting slag is in the form of aluminum corundum.
4. A method for preparing engineering material bricks after detoxifying chromium smelting slag, characterized in that, The method includes the following steps: Step 1: Dissolving hexavalent chromium by acid leaching. The chromium smelting slag was crushed and passed through a 2mm sieve to prepare a leachate for testing. The hexavalent chromium concentration was 161 mg / L. The chromium smelting slag and phosphoric acid were mixed in a weight ratio of 100:4 and soaked for 24 hours. Step 2: Reduction and detoxification were carried out using aluminum powder as a reducing agent. The aluminum powder particle size was 100 mesh sieve, and the amount of aluminum powder added was 1% of the dry basis smelting slag weight. The aluminum powder and the chromium smelting slag soaked in phosphoric acid were mixed evenly using a mixer. The mixture was then pressed into 6 pieces using a press, each piece measuring 460mm×150mm×75mm. The pieces were placed in a drying oven for 24 hours to dry, and then placed in a calcining furnace at a constant temperature of 1210℃ for 6 hours to prepare corundum slag bricks. After cooling, a leachate was prepared and tested. The results showed that the total chromium was 0.16mg / L, hexavalent chromium was 0.03mg / L, and barium was 0.2mg / L. Step 3: Test the density and refractoriness of corundum slag bricks. The density of corundum slag bricks is 3.7 g / cm3, which is dense and without pores; the refractoriness is 1860℃; after detoxification, corundum slag bricks are used as refractory materials; in the metallic chromium smelting slag, the alumina content reaches 80% and the ferric oxide content is less than 2%; the alumina in the metallic chromium smelting slag is in the form of aluminum corundum.
5. A method for preparing engineering material bricks after detoxifying chromium smelting slag, characterized in that, The method includes the following steps: Step 1: Dissolving hexavalent chromium by acid leaching. The chromium smelting slag was crushed and passed through a 2mm sieve to prepare a leachate for testing. The hexavalent chromium concentration was 769 mg / L. The chromium smelting slag and phosphoric acid were mixed in a weight ratio of 100:8 and soaked for 24 hours. Step 2: Reduction and detoxification were carried out using aluminum powder and magnesium powder as reducing agents. The aluminum powder particle size was 100 mesh sieve, and the amount of aluminum powder added was 1% of the dry basis smelting slag weight. The magnesium powder particle size was 100 mesh sieve, and the amount of magnesium powder added was 1% of the dry basis smelting slag weight. The aluminum powder, magnesium powder, and phosphoric acid-soaked metallic chromium smelting slag were mixed evenly using a mixer. The mixture was then pressed into 6 blocks using a press, each block measuring 460mm × 150mm × 75mm. The blocks were dried in a drying oven for 24 hours, and then placed in a calcining furnace at a constant temperature of 1300℃ for 6 hours to prepare corundum slag bricks. After cooling, a leachate was prepared and tested. The results showed that the total chromium was 0.2mg / L, hexavalent chromium was 0.08mg / L, and barium was 0.2mg / L. Step 3: Test the density and refractoriness of corundum slag bricks. The density of corundum slag bricks is 4.4 g / cm3, which is dense and without pores; the refractoriness is 1860℃; after detoxification, corundum slag bricks are used as refractory materials; in the metallic chromium smelting slag, the alumina content reaches 80% and the ferric oxide content is less than 2%; the alumina in the metallic chromium smelting slag is in the form of aluminum corundum.
Citation Information
Patent Citations
Chromic slag treatment process by blast furnace reduction method
CN101397607A
Method and special system for harmlessly comprehensively utilizing chromium slag
CN106316434A
Slag detoxification method and low-carbon ferrochrome production method
WO2021010312A1
Method for removing toxic pollutants in chromium metal smelting waste residues
CN119972760A